Response Time Relationship Time Nurse with Success Cardiac Arrest Patient Management in the Emergency Unit - Asrianto Asrianto; Rosida Rosida; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Cardiac arrest is an emergency that requires immediate and appropriate treatment. One key factor in the success of cardiopulmonary resuscitation (CPR) is the speed of response of nurses in the Emergency Department (ER). Response time Fast time) is associated with an increased chance of successful treatment of cardiac arrest patients. Objective: This study aims to determine the relationship between nurse response time and the success of treating cardiac arrest patients in the ER. Methods: This study used an observational analytical design with a cross-sectional approach. The sample was 40 cardiac arrest patients treated in the Emergency Department of Hospital